The Yin and Yang in plant breeding: the trade-off between plant growth yield and tolerance to stresses. (2019) - Silva, Aline Cunha da; Lima, Marcelo de Freitas; Eloy, Nubia Barbosa; Thiebaut, Flávia; Montessoro, Patrícia; Hemerly, Adriana Silva; Ferreira, Paulo Cavalcanti Gomes
Abstract: Plants have the ability to recognize and respond to biotic and abiotic stresses that are responsible for considerable yield losses in agriculture. Currently, a central goal of crop deployment is to develop the capacity to be tolerant to multiple stresses without a reduction in fitness. Still, many efforts to release such plants have failed because, frequently, there is a trade-off between growth and tolerance to stresses. Conventional breeding plays an essential role in crop improvement, but it is necessary to develop new tools, using for instance CRISPR, to produce new cultivars exhibiting tolerance to stress without significant yield penalty. In this short review we discuss novel strategies that can be employed to produce novel cultivars that would increase plant productivity without being hindered by potential negative effects of the immune response on plant development.